STUDI PENGOLAHAN LIMBAH CAIR PENYAMAKAN KULITDI PT BUDI MAKMUR KECAMATAN GEDONG KUNING YOGYAKARTA TAHUN 2014 - Sri Rezeki Indah Astiani; Djamaluddin Ramlan (Poltekkes Kemenkes Semarang, 2015)
PT Budi Makmur is one of the made leather industry that located in Yogyakarta. Itprocessing a raw leather which from goat leather that processed into wolves, shoes, etc. PT BudiMakmur also produce water waste that flows to the river and if the waste is not produced in the rightway, the waste will be very dangerous for the ecosystem in that river.The aim of this research areto know the process of the liquid waste producing leather tanning, the parameter of the liquid wastebefore and after through the producing process (COD, BOD, TSS dan pH) , and the condition of the liquidwaste producing leather tanning.The kind of this research is descriptive. The research done by collecting the field data anlaboratorium, and then analyzed and compared with the existing theory and quality of the liquid wasteproducing leather tanning.The result show that the source of the waste produce from the leather tranning. Liquid waste thatproduced is about 8.000-12.000 gallon per 1.000 wet leather pond that produced. The quality of theinfluent is BOD 1.946mg/lt, COD 1965mg/lt, TSS 1.774mg/ltd and pH 7.50. The quality of the effluent isBOD 98.61mg/lt, COD 100mg/lt, TSS 1130mg/lt and pH 7,49. The step of the liquid wasteprocessing are: filtering ink, equalitation ink, sedimentation, aeration and active mud.The writer conclude that PT Budi Makmur has already optimal to decrease the content thatcontained in the leather-liquid waste producing but the effluent that is produced still exceed the exsistingstandart quality. The suggestion to PT Budi Makmur is to more care about the liquid waste producing.